The Effect of Business Strategy and Management Control Systems Misfit On Hotel Performance - Adiputra, I Made Pradana; Gani, Lindawati; Rossieta, Hilda (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this research is to test the level of misfit business strategy with management control system will negatively associate to company performance. This study contributes to the existence of an empirical test of the existence of the concept of business strategy misfit with the management control system will negatively associate the company performance based on contingency-fit approach. In addition, the results of this study are expected to be a consideration for managers in the service industry to consider contingency factors in organizational design to improve company performance. The research was conducted by survey method (questionnaire) and purposive sampling at 227 star hotels industry type in Bali which sourced from Tourism Office of Bali Province 2018. Research respondents are senior managers with a minimum 1 year working period and have comprehensive information on company policies and operations. Using statistical method of regression with residual approach (bivariate analysis), the result of research indicate thatÃ‚Â the result of research show according to hypothesis in research that there is influence of strategic misfit business with MCS negatively affect to financial performance and non- financial performance in hotel industry in Bali.